Review of the VO2 smart material applications with emphasis on its use for spacecraft thermal control - Haddad, Emile; Kruzelecky, Roman V.; Murzionak, Piotr; Jamroz, Wes; Tagziria, Kamel; Chaker, Mohamed; Ledrogoff, Boris (Frontiers in Materials, 2022)
It is surprising to see the wide range and versatile potential of applications of the VO2, due to its transition from a semiconductor phase at low temperature, to a metallic state at high temperature. Although this transition’s atomic mechanism is not yet well understood, the tuneability is very reproducible experimentally and can be monitored by various triggering schemes, not only by heating/cooling but also by applying a voltage, pressure, or high power single fast photonic pulse. Many of the recent applications use not only the low-temperature phase and the high-temperature phase, but also the transition slope to monitor a specific parameter. The paper starts with a summary of the VO2 thin film deposition methods and a table presenting its recent proposed applications, some of which our team had worked on. Then the development characterization and application of the VO2 as a smart thermal radiator is provided along with the recent progress. The experimental results of the emissivity were measured at low temperature and high temperature, as well as during the transition in vacuum based on the thermal power balance. These measurements were compared with those deduced from an average of Infrared Reflectance (2-30µm) weighed with the blackbody reflection spectrum. The roadmap is to try alternatives of the multilayers in order to increase the emissivity tuneability, increase the device dimensions, have an easier application on space surfaces, while lowering cost.